On two enigmatic spiders (Araneae: Cybaeidae & Phrurolithidae) from the Russian Far East - Marusik, Yuri M.; Omelko, Mikhail M.; Koponen, Seppo (Zootaxa, 2020)
Cybaeota Chamberlin & Ivie, 1933, a genus previously known only in the Nearctic, has been found in the Maritime Province of Russia for the first time. It is represented by a new species, C. wesolowskae sp. nov. (♂♀), which is close to the generotype, C. calcarata (Emerton, 1911). Additionally, a new species, Phrurolithus lindemanni sp. nov. (♀), is described from the Maritime Province as well. It has unusually light colouration in comparison to other congeners. Trans-Pacific disjunctive ranges on species, genus and family levels in arthropods are briefly discussed.